Recycled aggregate strengthening method based on regulation and control of hydration process of alkali-activated cementing material

Through the hydration process regulation method based on alkali-excited gelling materials, ultrasonic assisted technology is used to diffuse the depolymerized monomer into the pores and cracks of the regenerated aggregate, achieving nano-level repolymerization and strengthening, solving the problem of nanomaterial aggregation, improving the strengthening efficiency of regenerated aggregates and reducing costs.

CN119822702AActive Publication Date: 2025-04-15SHANDONG UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510079013.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-15
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

There are agglomeration problems in existing nanomaterial reinforced regenerated aggregates, which leads to poor reinforcement effects and high cost, making it difficult to promote and apply.

Method used

The hydration process regulation method based on alkali-excited gelling materials is adopted to diffuse the depolymerized monomer into the pores and fissures of the regenerated aggregate through ultrasonic assistance, achieving nano-level repolymerization strengthening.

Benefits of technology

It effectively solves the problem of nanomaterial aggregation, improves the strengthening efficiency of regenerated aggregates, reduces costs, and achieves efficient and low-cost regenerated aggregate reinforcement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822702A_ABST
    Figure CN119822702A_ABST
Patent Text Reader

Abstract

The invention relates to a recycled aggregate strengthening method based on alkali-activated cementing material hydration process regulation and control, and belongs to the technical field of building material preparation and solid waste resource utilization. Mixing the alkali-activated cementing material with water according to a water-cement ratio of (0.5-5.0): 1 to prepare an alkali-activated cementing material solution; and adding the recycled aggregate into the alkali-activated cementing material solution according to the mass ratio of the recycled aggregate to the alkali-activated cementing material being (1.1-2.5): 1, reinforcing by adopting a slurry coating method, and then drying and curing to obtain the alkali-activated cementing material. According to the method disclosed by the invention, the nano-scale depolymerization monomer in the hydration process of the alkali-activated cementing material is diffused into residual mortar pores and aggregate microcracks, and then the recycled aggregate is reinforced through the repolymerization process of the depolymerization monomer, so that efficient and low-cost reinforcement of the recycled aggregate is realized, and high-quality recycling of waste concrete is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a recycled aggregate strengthening method based on regulating the hydration process of alkali-activated cementitious materials, and belongs to the technical field of building material preparation and solid waste resource utilization. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Recycling of waste concrete can reduce the use of natural sand and gravel aggregates, and can also help solve the environmental problems caused by the storage of waste concrete. The surface of recycled aggregate is covered with a considerable amount of old cement mortar, and the crushing process causes defects in the aggregate, which are manifested as low apparent density, high water absorption rate, and high crushing value. After the recycled aggregate concrete hardens, the internal pores increase, the mechanical strength decreases, and the durability deteriorates. These shortcomings limit the large-scale use of recycled aggregates. In order to improve the utilization rate and added value of waste concrete, the recycled aggregate prepared from waste concrete needs to be strengthened.

[0004] According to the inventors’ research, the current methods of strengthening recycled aggregates include mechanical grinding, acid treatment, heated grinding, carbonization modification, nanomaterial modification, microbial modification, etc. Among them, nanomaterial modification is an efficient method of strengthening recycled aggregates. However, there are problems with nanomaterial modification: 1. Nanomaterials are easy to agglomerate, and the dispersion effect in residual mortar and microcracks is poor, resulting in poor strengthening effect; 2. Nanomaterials are expensive, which makes it difficult to promote and apply the strengthened recycled aggregates. Therefore, it is necessary to improve the existing technology of strengthening recycled aggregates with nanomaterials, and provide a new method of strengthening recycled aggregates that improves the water absorption rate and crushing value of recycled aggregates. Summary of the invention

[0005] In order to solve the shortcomings of the existing nanomaterial reinforced aggregate technology, the purpose of the present invention is to provide a recycled aggregate reinforcement method based on the regulation of the hydration process of alkali-activated cementitious materials. Based on the depolymerization-repolymerization process of alkali-activated cementitious materials, the nano-scale depolymerized monomers in the hydration process of alkali-activated cementitious materials are diffused into the residual mortar pores and aggregate microcracks, and then the recycled aggregate is reinforced through the repolymerization process of the depolymerized monomers, thereby achieving efficient and low-cost reinforcement of the recycled aggregate and promoting high-quality recycling of waste concrete.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] In the first aspect, a method for strengthening recycled aggregate based on the regulation of the hydration process of alkali-activated cementitious material is provided, wherein the alkali-activated cementitious material is mixed with water at a water-cement ratio of 0.5 to 5:1 to prepare an alkali-activated cementitious material solution; the recycled aggregate is added to the alkali-activated cementitious material solution in a mass ratio of 1.1 to 2.5:1, and then strengthened by a slurry coating method, followed by drying and curing to obtain the obtained product;

[0008] The strengthening procedure is: turn on ultrasound, first strengthen the surface of the substrate under the condition of 10-20°C for 50-70 minutes with ultrasound assistance, then strengthen the surface of the substrate under the condition of 20-30°C for 50-70 minutes with ultrasound assistance, then turn off ultrasound, and strengthen the surface of the substrate under the condition of 60-70°C for 500-600 minutes;

[0009] The raw materials of the alkali-activated gelling material include, by mass fraction, 80-90 parts of silicoaluminate components, 9-15 parts of alkaline activator, and 1-5 parts of setting time regulator; the raw materials of the alkaline activator include, by mass fraction, 25-30 parts of sodium silicate, 15-20 parts of sodium carbonate, 4-9 parts of aluminum sulfate, and 0-8 parts of calcium sulfate; the raw materials of the setting time regulator include, by mass fraction, 30-40 parts of glucose, 25-30 parts of sodium gluconate, and 30-45 parts of sodium hexametaphosphate.

[0010] The silicoaluminous component of the present invention is a substance whose main components contain aluminum and / or silicon, and can be industrial solid wastes such as blast furnace slag, fly ash, steel slag, coal gangue, red mud, etc.

[0011] In a second aspect, a reinforced recycled aggregate is obtained by the above-mentioned recycled aggregate reinforcement method.

[0012] The third aspect is the application of reinforced recycled aggregate in concrete.

[0013] The beneficial effects of the present invention are:

[0014] (1) The traditional nanomaterial strengthening method is to directly add nanomaterials for strengthening and modification, so there is a problem that nanomaterials are easy to agglomerate. The present invention provides a recycled aggregate nano-strengthening method based on alkali-activated gelling material dissolution-diffusion-polymerization. The reaction principle of alkali-activated gelling material is that the silicon-aluminum components depolymerize under the action of an alkaline activator to generate nano-scale aluminum oxide tetrahedrons and silicon oxide tetrahedrons, and then the depolymerized aluminum oxide tetrahedrons and silicon oxide tetrahedrons undergo polymerization to generate a geopolymer gel with a three-dimensional network structure. The technical feature of the present invention is to generate nano-scale strengthening materials in situ, and then polymerize in situ, and finally strengthen the aggregate, which solves the agglomeration problem caused by the traditional nanomaterial strengthening process and improves the strengthening efficiency of the recycled aggregate.

[0015] (2) The technology of strengthening recycled aggregate with traditional alkali-activated cementitious materials is mainly based on the principle of paste coating, which has problems such as uneven paste coating thickness and large differences in strengthening effect. The present invention adjusts the water-cement ratio in the alkali-activated cementitious materials and adds a compounded setting time regulator to control the hydration process of the alkali-activated cementitious materials, prolong the existence time of aluminum oxide tetrahedron and silicon oxide tetrahedron, and improves the diffusion rate of aluminum oxide tetrahedron and silicon oxide tetrahedron through the improvement of ultrasonic method, so that they can enter the pores and cracks of the recycled aggregate more efficiently, thereby forming a new strengthening process technology based on nanomaterial strengthening and supplemented by paste coating strengthening, which improves the strengthening effect of recycled aggregate.

[0016] (3) Alkali activators are used in traditional alkali-activated cementitious material systems, which makes the recycled concrete prepared by them prone to alkali-aggregate reaction. The present invention innovatively proposes the idea of ​​alkali-salt synergistic activation, and uses an alkali-salt composite activator composed of sodium silicate, sodium carbonate, aluminum sulfate, and calcium sulfate to significantly reduce the alkalinity of the recycled concrete system, thereby avoiding the alkali-aggregate reaction in the recycled concrete caused by the use of traditional single-type alkali activators such as sodium hydroxide and sodium silicate.

[0017] (4) The cost of traditional nanomaterial-reinforced recycled aggregates is relatively high. The present invention uses alkali-activated cementitious materials and can use industrial solid waste as raw materials, which has the advantages of low cost, ability to absorb solid waste, and significant ecological benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0019] Figure 1 The schematic diagram of the mechanism of strengthening recycled aggregate based on the regulation of hydration process of alkali-activated cementitious material in the present invention. DETAILED DESCRIPTION

[0020] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0021] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0022] Recycled aggregate has a large water absorption rate and a high crushing value, and the strengthening effect of existing nano-modified reinforced recycled aggregate is not ideal, and there is still a big difference in performance with natural aggregate. The main reason is that the nano-material has a small particle size and is easy to agglomerate, resulting in poor dispersion in residual mortar and microcracks, which is not conducive to the strengthening of recycled aggregate. The present invention proposes a recycled aggregate strengthening method based on the regulation of the hydration process of alkali-activated cementitious materials.

[0023] A typical embodiment of the present invention provides a method for strengthening recycled aggregate based on the regulation of the hydration process of alkali-activated cementitious material, wherein the alkali-activated cementitious material and water are mixed at a water-cement ratio of 0.5 to 5:1 to prepare an alkali-activated cementitious material solution; the recycled aggregate is added to the alkali-activated cementitious material solution at a mass ratio of the recycled aggregate to the alkali-activated cementitious material of 1.1 to 2.5:1, and then the recycled aggregate is strengthened, and then dried and cured to obtain the obtained product;

[0024] The strengthening procedure is: turn on ultrasound, first strengthen the surface of the substrate under the condition of 10-20°C for 50-70 minutes with ultrasound assistance, then strengthen the surface of the substrate under the condition of 20-30°C for 50-70 minutes with ultrasound assistance, then turn off ultrasound, and strengthen the surface of the substrate under the condition of 60-70°C for 500-600 minutes;

[0025] The raw materials of the alkali-activated gelling material include, by mass fraction, 80-90 parts of silicoaluminate components, 9-15 parts of alkaline activator, and 1-5 parts of setting time regulator; the raw materials of the alkali salt composite activator include, by mass fraction, 25-30 parts of sodium silicate, 15-20 parts of sodium carbonate, 4-9 parts of aluminum sulfate, and 0-8 parts of calcium sulfate; the raw materials of the setting time regulator include, by mass fraction, 30-40 parts of glucose, 25-30 parts of sodium gluconate, and 30-45 parts of sodium hexametaphosphate.

[0026] In some embodiments, in the alkali-activated gelling material, the Si / Al atomic ratio is 1 to 2:1, and the Si / Ca atomic ratio is 0.2 to 1.5:1, so as to ensure that the alkali-activated gelling material has a high mechanical strength.

[0027] In some embodiments, the siliceous and aluminous components are one or more of blast furnace slag, fly ash, steel slag, coal gangue, and red mud.

[0028] In some embodiments, the specific surface area of ​​the silicon-aluminum component is 600 to 1000 m 2 / kg, moisture content is less than 2%.

[0029] In some embodiments, the alkali-activated cementitious material has an initial setting time of 300 to 480 minutes and a final setting time of 500 to 600 minutes, thereby ensuring that the alkali-activated cementitious material has the advantages of a long initial setting time and a short final setting time, and ensuring that the depolymerized monomers diffuse better into the pores and cracks of the recycled aggregate.

[0030] The recycled aggregate of the present invention is obtained by crushing and screening waste concrete. In some embodiments, the particle sizes of the recycled aggregate are screened into 0-4.75 mm, 4.75-9.5 mm, 9.5-19 mm, and 19-31.5 mm for strengthening respectively.

[0031] Another embodiment of the present invention provides a reinforced recycled aggregate obtained by the above-mentioned recycled aggregate reinforcement method.

[0032] In some embodiments, the water absorption of the reinforced recycled aggregate is 0.96-1.26%, and the crushing value is 8.82-10.52%.

[0033] A third embodiment of the present invention provides an application of reinforced recycled aggregate in concrete.

[0034] In some embodiments, the concrete is ultra high performance concrete.

[0035] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.

[0036] Embodiment 1:

[0037] (1) The waste concrete is screened and impurities are removed, and then crushed by a jaw crusher to obtain recycled aggregates with particle sizes of 0-4.75 mm, 4.75-9.5 mm, 9.5-19 mm, and 19-31.5 mm. The recycled aggregates are rinsed and air-dried to constant weight for later use.

[0038] (2) Prepare blast furnace slag powder and fly ash composite with Si / Al ratio of 1 and Si / Ca ratio of 0.2 as the raw materials of silicon-aluminum component and grind them to a specific surface area of ​​600m 2 / kg, for spare use.

[0039] (3) Weigh 30 parts of sodium silicate, 20 parts of sodium carbonate, 9 parts of aluminum sulfate, and 8 parts of calcium sulfate, mix them evenly, and prepare an alkali-salt composite activator for use.

[0040] (4) Weigh 30 parts of glucose, 25 parts of sodium gluconate, and 45 parts of sodium hexametaphosphate, mix them evenly, and prepare a setting time regulator for later use.

[0041] (5) Prepare an alkali-activated gelling material according to 80 parts of alumina-silica component, 15 parts of an alkali-salt composite activator, and 5 parts of a setting time regulator, and set aside.

[0042] (6) Prepare an alkali-activated cementitious material slurry solution at a water-cement ratio of 0.5.

[0043] (7) Recycled aggregate was added to the cementitious material solution at a mass ratio of 1.5:1, and the ultrasonic system was turned on at the same time. The slurry temperature was 10°C from 0 to 60 minutes and 20°C from 60 to 120 minutes. After 120 minutes, the ultrasonic system was turned off, the temperature was 60°C, and strengthening was continued for 500 minutes.

[0044] (8) The reinforced recycled aggregate is cured under standard conditions (temperature 20±3℃, relative humidity maintained above 90%) for 7 days, dried with hot air, and then it can be used.

[0045] Embodiment 2:

[0046] (1) The waste concrete is screened and impurities are removed, and then crushed by a jaw crusher to obtain recycled aggregates with particle sizes of 0-4.75 mm, 4.75-9.5 mm, 9.5-19 mm, and 19-31.5 mm. The recycled aggregates are rinsed and air-dried to constant weight for later use.

[0047] (2) Prepare blast furnace slag powder and fly ash composite with Si / Al ratio of 1 and Si / Ca ratio of 0.2 as the raw materials of silicon-aluminum component and grind them to a specific surface area of ​​600m 2 / kg, for spare use.

[0048] (3) Weigh 30 parts of sodium silicate, 20 parts of sodium carbonate, 9 parts of aluminum sulfate, and 8 parts of calcium sulfate, mix them evenly, and prepare an alkali-salt composite activator for use.

[0049] (4) Weigh 35 parts of glucose, 27 parts of sodium gluconate, and 30 parts of sodium hexametaphosphate, mix them evenly, and prepare a setting time regulator for later use.

[0050] (5) Prepare an alkali-activated cementitious material according to 90 parts of alumina-silica component, 9 parts of an alkali-salt composite activator, and 1 part of a setting time regulator, and set aside.

[0051] (6) Prepare an alkali-activated cementitious material slurry solution at a water-cement ratio of 0.5.

[0052] (7) Recycled aggregate was added to the cementitious material solution at a mass ratio of 1.5:1, and the ultrasonic system was turned on at the same time. The slurry temperature was 10°C from 0 to 60 minutes and 20°C from 60 to 120 minutes. After 120 minutes, the ultrasonic system was turned off, the temperature was 60°C, and strengthening was continued for 500 minutes.

[0053] (8) The reinforced recycled aggregate is cured under standard conditions (temperature 20±3℃, relative humidity maintained above 90%) for 7 days, dried with hot air, and then it can be used.

[0054] Embodiment 3:

[0055] (1) The waste concrete is screened and impurities are removed, and then crushed by a jaw crusher to obtain recycled aggregates with particle sizes of 0-4.75 mm, 4.75-9.5 mm, 9.5-19 mm, and 19-31.5 mm. The recycled aggregates are rinsed and air-dried to constant weight for later use.

[0056] (2) Prepare a red mud and coal gangue composite with Si / Al ratio of 1 and Si / Ca ratio of 0.2 as the raw material of the silicon-aluminum component and grind it to a specific surface area of ​​600 m 2 / kg, for spare use.

[0057] (3) Weigh 30 parts of sodium silicate, 20 parts of sodium carbonate, 9 parts of aluminum sulfate, and 8 parts of calcium sulfate, mix them evenly, and prepare an alkali-salt composite activator for use.

[0058] (4) Weigh 30 parts of glucose, 25 parts of sodium gluconate, and 45 parts of sodium hexametaphosphate, mix them evenly, and prepare a setting time regulator for later use.

[0059] (5) Prepare an alkali-activated cementitious material according to 89 parts of alumina-silica component, 9 parts of alkali-salt composite activator, and 2 parts of setting time regulator, and set aside.

[0060] (6) Prepare an alkali-activated cementitious material slurry solution at a water-cement ratio of 0.5.

[0061] (7) Recycled aggregate was added to the cementitious material solution at a mass ratio of 1.5:1, and the ultrasonic system was turned on at the same time. The slurry temperature was 10°C from 0 to 60 minutes and 20°C from 60 to 120 minutes. After 120 minutes, the ultrasonic system was turned off, the temperature was 60°C, and the strengthening was continued for 500 minutes.

[0062] (8) The reinforced recycled aggregate is cured under standard conditions (temperature 20±3℃, relative humidity maintained above 90%) for 7 days, dried with hot air, and then it can be used.

[0063] Embodiment 4:

[0064] (1) The waste concrete is screened and impurities are removed, and then crushed by a jaw crusher to obtain recycled aggregates with particle sizes of 0-4.75 mm, 4.75-9.5 mm, 9.5-19 mm, and 19-31.5 mm. The recycled aggregates are rinsed and air-dried to constant weight for later use.

[0065] (2) Prepare blast furnace slag powder and fly ash composite with Si / Al ratio of 2 and Si / Ca ratio of 1.5 as the raw materials of silicon-aluminum component and grind them to a specific surface area of ​​600m 2 / kg, for spare use.

[0066] (3) Weigh 25 parts of sodium silicate, 15 parts of sodium carbonate, and 4 parts of aluminum sulfate, mix them evenly, and prepare an alkali-salt composite activator for use.

[0067] (4) Weigh 30 parts of glucose, 25 parts of sodium gluconate, and 45 parts of sodium hexametaphosphate, mix them evenly, and prepare a setting time regulator for later use.

[0068] (5) Prepare an alkali-activated cementitious material according to 90 parts of alumina-silica component, 9 parts of an alkali-salt composite activator, and 1 part of a setting time regulator, and set aside.

[0069] (6) Prepare an alkali-activated cementitious material slurry solution at a water-cement ratio of 0.5.

[0070] (7) Recycled aggregate was added to the cementitious material solution at a mass ratio of 1.5:1, and the ultrasonic system was turned on at the same time. The slurry temperature was 10°C from 0 to 60 minutes and 20°C from 60 to 120 minutes. After 120 minutes, the ultrasonic system was turned off, the temperature was 60°C, and strengthening was continued for 500 minutes.

[0071] (8) The reinforced recycled aggregate can be used after being cured under standard conditions (temperature 20±3℃, relative humidity maintained above 90%) for 7 days.

[0072] Embodiment 5:

[0073] (1) The waste concrete is screened and impurities are removed, and then crushed by a jaw crusher to obtain recycled aggregates with particle sizes of 0-4.75 mm, 4.75-9.5 mm, 9.5-19 mm, and 19-31.5 mm. The recycled aggregates are rinsed and air-dried to constant weight for later use.

[0074] (2) Prepare blast furnace slag powder and fly ash composite with Si / Al ratio of 1 and Si / Ca ratio of 0.2 as the raw materials of silicon-aluminum component and grind them to a specific surface area of ​​600m 2 / kg, for spare use.

[0075] (3) Weigh 30 parts of sodium silicate, 20 parts of sodium carbonate, 9 parts of aluminum sulfate, and 2 parts of calcium sulfate, mix them evenly, and prepare an alkali-salt composite activator for use.

[0076] (4) Weigh 30 parts of glucose, 25 parts of sodium gluconate, and 45 parts of sodium hexametaphosphate, mix them evenly, and prepare a setting time regulator for later use.

[0077] (5) Prepare an alkali-activated cementitious material according to 90 parts of alumina-silica component, 9 parts of an alkali-salt composite activator, and 1 part of a setting time regulator, and set aside.

[0078] (6) Prepare an alkali-activated cementitious material slurry solution at a water-cement ratio of 0.5.

[0079] (7) Recycled aggregate was added to the cementitious material solution at a mass ratio of 1.5:1, and the ultrasonic system was turned on at the same time. The slurry temperature was 10°C from 0 to 60 minutes and 20°C from 60 to 120 minutes. After 120 minutes, the ultrasonic system was turned off, the temperature was 60°C, and strengthening was continued for 500 minutes.

[0080] (8) The reinforced recycled aggregate is cured under standard conditions (temperature 20±3℃, relative humidity maintained above 90%) for 7 days, dried with hot air, and then it can be used.

[0081] Embodiment 6:

[0082] (1) The waste concrete is screened and impurities are removed, and then crushed by a jaw crusher to obtain recycled aggregates with particle sizes of 0-4.75 mm, 4.75-9.5 mm, 9.5-19 mm, and 19-31.5 mm. The recycled aggregates are rinsed and air-dried to constant weight for later use.

[0083] (2) Prepare blast furnace slag powder and fly ash composite with Si / Al ratio of 1 and Si / Ca ratio of 0.2 as the raw materials of silicon-aluminum component and grind them to a specific surface area of ​​600m 2 / kg, for spare use.

[0084] (3) Weigh 25 parts of sodium silicate, 20 parts of sodium carbonate, 9 parts of aluminum sulfate, and 8 parts of calcium sulfate, mix them evenly, and prepare an alkali-salt composite activator for use.

[0085] (4) Weigh 40 parts of glucose, 30 parts of sodium gluconate, and 30 parts of sodium hexametaphosphate, mix them evenly, and prepare a setting time regulator for later use.

[0086] (5) Prepare an alkali-activated cementitious material according to 90 parts of alumina-silica component, 9 parts of an alkali-salt composite activator, and 1 part of a setting time regulator, and set aside.

[0087] (6) Prepare an alkali-activated cementitious material slurry solution at a water-cement ratio of 0.5.

[0088] (7) Recycled aggregate was added to the cementitious material solution at a mass ratio of 1.5:1, and the ultrasonic system was turned on at the same time. The slurry temperature was 10°C from 0 to 60 minutes and 20°C from 60 to 120 minutes. After 120 minutes, the ultrasonic system was turned off, the temperature was 60°C, and strengthening was continued for 500 minutes.

[0089] (8) The reinforced recycled aggregate is cured under standard conditions (temperature 20±3℃, relative humidity maintained above 90%) for 7 days, dried with hot air, and then it can be used.

[0090] Embodiment 7:

[0091] (1) The waste concrete is screened and impurities are removed, and then crushed by a jaw crusher to obtain recycled aggregates with particle sizes of 0-4.75 mm, 4.75-9.5 mm, 9.5-19 mm, and 19-31.5 mm. The recycled aggregates are rinsed and air-dried to constant weight for later use.

[0092] (2) Prepare blast furnace slag powder and fly ash composite with Si / Al ratio of 1 and Si / Ca ratio of 0.2 as the raw materials of silicon-aluminum component and grind them to a specific surface area of ​​600m 2 / kg, for spare use.

[0093] (3) Weigh 27 parts of sodium silicate, 15 parts of sodium carbonate, 9 parts of aluminum sulfate, and 8 parts of calcium sulfate, mix them evenly, and prepare an alkali-salt composite activator for use.

[0094] (4) Weigh 30 parts of glucose, 25 parts of sodium gluconate, and 45 parts of sodium hexametaphosphate, mix them evenly, and prepare a setting time regulator for later use.

[0095] (5) Prepare an alkali-activated cementitious material according to 90 parts of alumina-silica component, 9 parts of an alkali-salt composite activator, and 1 part of a setting time regulator, and set aside.

[0096] (6) Prepare an alkali-activated cementitious material slurry solution at a water-cement ratio of 1.0.

[0097] (7) Recycled aggregate was added to the cementitious material solution at a mass ratio of 1.5:1, and the ultrasonic system was turned on at the same time. The slurry temperature was 10°C from 0 to 60 minutes and 20°C from 60 to 120 minutes. After 120 minutes, the ultrasonic system was turned off, the temperature was 60°C, and the strengthening was continued for 500 minutes.

[0098] (8) The reinforced recycled aggregate is cured under standard conditions (temperature 20±3℃, relative humidity maintained above 90%) for 7 days, dried with hot air, and then it can be used.

[0099] Embodiment 8:

[0100] (1) The waste concrete is screened and impurities are removed, and then crushed by a jaw crusher to obtain recycled aggregates with particle sizes of 0-4.75 mm, 4.75-9.5 mm, 9.5-19 mm, and 19-31.5 mm. The recycled aggregates are rinsed and air-dried to constant weight for later use.

[0101] (2) Prepare blast furnace slag powder and fly ash composite with Si / Al ratio of 1 and Si / Ca ratio of 0.2 as the raw materials of silicon-aluminum component and grind them to a specific surface area of ​​600m 2 / kg, for spare use.

[0102] (3) Weigh 27 parts of sodium silicate, 15 parts of sodium carbonate, 4 parts of aluminum sulfate, and 8 parts of calcium sulfate, mix them evenly, and prepare an alkali-salt composite activator for use.

[0103] (4) Weigh 30 parts of glucose, 25 parts of sodium gluconate, and 45 parts of sodium hexametaphosphate, mix them evenly, and prepare a setting time regulator for later use.

[0104] (5) Prepare an alkali-activated cementitious material according to 90 parts of alumina-silica component, 9 parts of an alkali-salt composite activator, and 1 part of a setting time regulator, and set aside.

[0105] (6) Prepare an alkali-activated cementitious material slurry solution at a water-cement ratio of 0.5.

[0106] (7) Recycled aggregate was added to the cementitious material solution at a mass ratio of 3:1, and the ultrasonic system was turned on at the same time. The slurry temperature was 10°C from 0 to 60 minutes and 20°C from 60 to 120 minutes. After 120 minutes, the ultrasonic system was turned off, the temperature was 60°C, and the strengthening was continued for 500 minutes.

[0107] (8) The reinforced recycled aggregate is cured under standard conditions (temperature 20±3℃, relative humidity maintained above 90%) for 7 days, dried with hot air, and then it can be used.

[0108] Embodiment 9:

[0109] (1) The waste concrete is screened and impurities are removed, and then crushed by a jaw crusher to obtain recycled aggregates with particle sizes of 0-4.75 mm, 4.75-9.5 mm, 9.5-19 mm, and 19-31.5 mm. The recycled aggregates are rinsed and air-dried to constant weight for later use.

[0110] (2) Prepare blast furnace slag powder and fly ash composite with Si / Al ratio of 1 and Si / Ca ratio of 0.2 as the raw materials of silicon-aluminum component and grind them to a specific surface area of ​​600m 2 / kg, for spare use.

[0111] (3) Weigh 25 parts of sodium silicate, 18 parts of sodium carbonate, 4 parts of aluminum sulfate, and 5 parts of calcium sulfate, mix them evenly, and prepare an alkali-salt composite activator for use.

[0112] (4) Weigh 30 parts of glucose, 25 parts of sodium gluconate, and 45 parts of sodium hexametaphosphate, mix them evenly, and prepare a setting time regulator for later use.

[0113] (5) Prepare an alkali-activated cementitious material according to 90 parts of alumina-silica component, 9 parts of an alkali-salt composite activator, and 1 part of a setting time regulator, and set aside.

[0114] (6) Prepare an alkali-activated cementitious material slurry solution at a water-cement ratio of 0.5.

[0115] (7) Recycled aggregate was added to the cementitious material solution at a mass ratio of 1.5:1, and the ultrasonic system was turned on at the same time. The slurry temperature was 20°C from 0 to 60 minutes and 30°C from 60 to 120 minutes. After 120 minutes, the ultrasonic system was turned off, the temperature was 70°C, and the strengthening was continued for 500 minutes.

[0116] (8) The reinforced recycled aggregate is cured under standard conditions (temperature 20±3℃, relative humidity maintained above 90%) for 7 days, dried with hot air, and then it can be used.

[0117] The strengthening mechanism of Examples 1 to 9 is as follows Figure 1 shown.

[0118] Comparative Example 1:

[0119] Compared with Example 1, the activator adopts the traditional sodium silicate activator, and the alkali-salt composite activator is not used.

[0120] Comparative Example 2:

[0121] Compared with Example 1, no setting time regulator was added.

[0122] Comparative Example 3:

[0123] Compared with Example 1, the temperature during the strengthening process was always 20°C.

[0124] According to the relevant test methods in "Recycled coarse aggregate for concrete" GB / T 25177-2010, the crushing value and water absorption rate of natural aggregate, unreinforced recycled aggregate and recycled aggregate treated by the above-mentioned reinforcement method were tested.

[0125] The test results are shown in Table 1

[0126] The main physical properties of untreated recycled aggregate are: water absorption 10.25%, crushing value 28.0%. The main physical properties of natural aggregate are: water absorption 0.88%, crushing value 8.66%.

[0127] Table 1 Basic physical properties of different recycled aggregates

[0128]

[0129]

[0130] As shown in Table 1, in the recycled aggregate strengthening method based on the regulation of the setting time of alkali-activated cementitious materials in Examples 1 to 9, the water absorption rate and crushing value of the strengthened recycled aggregate are significantly reduced. Compared with the unreinforced aggregate, the minimum water absorption rate is 0.96%, and the minimum crushing value is 8.82%, reaching the Class I aggregate standard. The quality of the recycled aggregate is significantly improved, and it can completely replace natural aggregate in ultra-high performance concrete, thereby realizing the large-scale application of waste concrete.

[0131] The recycled aggregate reinforced by Example 6 and the natural aggregate were used to prepare ultra-high performance concrete according to Table 2. The test results are shown in Table 3.

[0132] Table 2 Ultra-high performance concrete mix ratio

[0133]

[0134] Table 3 Ultra-high performance concrete strength test results

[0135]

[0136] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for strengthening recycled aggregate based on the regulation of hydration process of alkali-activated cementitious materials, characterized in that: The alkali-activated cementitious material is mixed with water at a water-cement ratio of 0.5 to 5.0:1 to prepare an alkali-activated cementitious material solution; the recycled aggregate is added to the alkali-activated cementitious material solution at a mass ratio of 1.1 to 2.5:1 to strengthen the alkali-activated cementitious material by a slurry coating method, and then dried and cured to obtain the product; The strengthening procedure is: turn on ultrasound, first strengthen the surface of the substrate under the condition of 10-20°C for 50-70 minutes with ultrasound assistance, then strengthen the surface of the substrate under the condition of 20-30°C for 50-70 minutes with ultrasound assistance, then turn off ultrasound, and strengthen the surface of the substrate under the condition of 60-70°C for 500-600 minutes; The raw materials of the alkali-activated gelling material include, by mass fraction, 80-90 parts of silicoaluminate components, 9-15 parts of alkaline activator, and 1-5 parts of setting time regulator; the raw materials of the alkali salt composite activator include, by mass fraction, 25-30 parts of sodium silicate, 15-20 parts of sodium carbonate, 4-9 parts of aluminum sulfate, and 0-8 parts of calcium sulfate; the raw materials of the setting time regulator include, by mass fraction, 30-40 parts of glucose, 25-30 parts of sodium gluconate, and 30-45 parts of sodium hexametaphosphate.

2. The method for strengthening recycled aggregate based on the regulation of hydration history of alkali-activated cementitious materials according to claim 1, characterized in that: In the alkali-activated gelling material, the Si / Al atomic ratio is 1-2:1, and the Si / Ca atomic ratio is 0.2-1.5:

1.

3. The method for strengthening recycled aggregate based on the regulation of hydration history of alkali-activated cementitious materials as claimed in claim 1, characterized in that: The siliceous and aluminous components are one or more of blast furnace slag, fly ash, steel slag, coal gangue and red mud.

4. The method for strengthening recycled aggregate based on the regulation of hydration history of alkali-activated cementitious materials according to claim 1, characterized in that: The specific surface area of ​​the silicon-aluminum component is 600 to 1000 m 2 / kg, moisture content is less than 2%.

5. The method for strengthening recycled aggregate based on regulating the hydration process of alkali-activated cementitious materials according to claim 1, characterized in that: The initial setting time of the alkali-activated gelling material is 300 to 480 minutes, and the final setting time is 500 to 600 minutes.

6. The method for strengthening recycled aggregate based on regulating the hydration process of alkali-activated cementitious materials according to claim 1, characterized in that: The particle size of recycled aggregate shall not exceed 31.5 mm.

7. A reinforced recycled aggregate, characterized in that: Obtained by the recycled aggregate strengthening method according to any one of claims 1 to 6.

8. The reinforced recycled aggregate according to claim 7, characterized in that: The water absorption rate of the reinforced recycled aggregate is 0.96-1.26%, and the crushing value is 8.82-10.52%.

9. Use of the reinforced recycled aggregate according to claim 7 or 8 in concrete.

10. The use according to claim 9, characterized in that: The concrete is ultra-high performance concrete.

Citation Information

Patent Citations

  • Treatment method of volcanic-ash-paste-reinforced recycled concrete aggregate

    CN106007438A

  • Carbon-reduced recycled aggregate based on alkali excitation strengthening and preparation method of carbon-reduced recycled aggregate

    CN118420257A

  • Manufacturing method of recycled aggregate improved water absorption by coating alkali-activated binder

    KR101544494B1

  • AU2020103285A4